Molecular mechanism of DLBS3233 bioactive fraction in type-2 diabetes mellitus: network pharmacology and docking study - Tan, Santi; Tjandrawinata, Raymond Rubianto; Prasasty, Vivitri Dewi (Penerbit Universiti Kebangsaan Malaysia, 2023)
Although several antidiabetic agents are currently available, they commonly have undesirable effects and are not fully effective in reducing blood glucose. Therefore, since a long time ago, some Indonesians have preferred herbal medicine to cure and prevent diseases such as Lagerstroemia speciosa (L.) Pers. and Cinnamomum burmanni. (Nees & T.Nees) Blume, plants from Indonesia, are believed to be able to treat type 2 diabetes mellitus (T2DM). Both herbs are present in DLBS3233 bioactive fraction, a standardized herbal extract that acts as an insulin sensitizer like thiazolidinediones (TZDs). However, the molecular mechanisms, the bioactive compounds, and the target proteins involved remain unclear. To understand more about the potential molecular mechanism of DLBS3233 in treating T2DM, this network pharmacology study is conducted for the first time. Quercetin, kaempferol, and ellagic acid were discovered to have antidiabetic effects in this study as selected compounds of DLBS3233, p rimarily o n e ight c ore target proteins, including AKT1, EGFR, GSK3B, IL6, PTK2, RELA, SRC, and VEGFA. We also found that they exhibited ligand-receptor binding activity comparable to pioglitazone in the molecular docking study. Concisely, as a reference for furthering the development of this bioactive fraction, this study provides novel information on DLBS3233 in T2DM treatment that was not shown in prior studies.